Determinants of Carbon Emission Disclosure in Non-Financial Companies Listed on IDX - Nariswari, Anindya; Musyaffi, Ayatulloh Michael; Hasanah, Nuramalia (Journal of Environmental Economics and Sustainability, 2024)
According to a report by the Climate Transparency organization, Indonesia is in a critical situation. The organization states that the Indonesian government is not taking adequate steps to meet the Paris Agreement's target of limiting global temperature rise to 1.5°C. As the world's fifth-largest carbon emitter, Indonesia requires concrete actions to reduce its carbon emissions. One approach is to enhance the responsibility and accountability of companies in carbon-intensive industries to disclose their emissions. This study aims to identify the factors influencing carbon emission disclosure. The research uses a population of non-financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023, with 52 samples selected through purposive sampling. Multiple linear regression analysis is applied in this study to examine the relationship between the independent variables and the dependent variable. The results show that firm size affects carbon emission disclosure, while leverage and managerial ownership do not impact carbon emission disclosure.